Associative stigma in family members of psychotic patients in Flanders: An exploratory study - Catthoor, Kirsten (World J Psychiatry, 2015)
AIM: To assess presence and severity of associative stigma in family members of psychotic patients and factors for higher associative stigma. METHODS: Standardized semi-structured interview of 150 family members of psychotic patients receiving full time treatment. This study on associative stigma in family members of psychotic patients was part of a larger research program on the burden of the family, using “Interview for the Burden of the Family” and the chapters stigma, treatment and attribution from the “Family interview Schedule”. The respondents were relatives, one per patient, either partner or parent. The patients had been diagnosed with schizophrenia or schizo-affective disorder. All contacts with patients and relatives were in Dutch. Relatives were deemed suitable to participate in this research if they saw the patient at least once a week. Recruitment took place in a standardized way: after obtaining the patient’s consent, the relatives were approached to participate. The results were analyzed using SPSS Version 18.0. RESULTS: The prevalence of associative stigma in this sample is 86%. Feelings of depression in the majority of family members are prominent. Twenty-one point three percent experienced guilt more or less frequent, while shame was less pronounced. Also, 18.6% of all respondents indicated that they tried to hide the illness of their family member for others regularly or more. Three six point seven percent really kept secret about it in certain circumstances and 29.3% made efforts to explain what the situation or psychiatric condition of their family member really is like. Factors with marked significance towards higher associative stigma are a worsened relationship between the patient and the family member, conduct problems to family members, the patients’ residence in a residential care setting, and hereditary attributional factors like genetic hereditability and character. The level of associative stigma has significantly been predicted by the burden of aggressive disruptions to family housemates of the psychotic patient. CONCLUSION: Family members of psychotic patients in Flanders experience higher associative stigma compared to previous international research. Disruptive behavior by the patient towards in-housing family members is the most accurate predictor of higher associative stigma.